Assessment of Diagnostics Tools for Sarcopenia Severity Using the Item Response Theory (IRT) - Šteffl, Michal; Musálek, Martin; Kramperová, Veronika; Petr, Miroslav; Kohlíková, Eva; Holmerová, Iva; Volicer, Ladislav (The Journal of nutrition, health & aging, 2016)
OBJECTIVE: To use the item response theory (IRT) methods to examine the degree to which the four selected tools reflect sarcopenia and to arrange them according to their ability to estimate sarcopenia severity. DESIGN: A cross-sectional study aimed at verifying the possibilities of using diagnostic tools for sarcopenia. SETTING AND PARTICIPANTS: The study included residents living in an assisted living unit at the Senior Centre in Blansko (South Moravia, Czech Republic) (n=77). Sarcopenia was estimated according to the proposals of the European Working Group on Sarcopenia in Older People (EWGSOP) using calf circumference, the EWGSOP algorithm, hand grip strength, and the Short Physical Performance Battery (SPPB). RESULTS: The results from the IRT model showed that these four methods indicate strong unidimensionality so that they measure the same latent variable. The methods ranked according to the discrimination level ranging from high to low discrimination where the calf circumference was the most discriminatory (Hi = 0.86) and the SPPB together with hand grip strength were the least discriminatory (both Hi = 0.44). CONCLUSION: We are recommending to identify mild sarcopenia by SPPB or hand grip strength, moderate sarcopenia by the EWGSOP algorithm and severe sarcopenia by the calf circumference.
Keywords: Cross-Sectional Studies; sarkopenie; senioři nad 80 let; Humans; Prevalence; Aged, 80 and over; Hand Strength; Algorithms; síla ruky; mužské pohlaví; průřezové studie; Sarcopenia; ženské pohlaví; lidé; prevalence; Aged; senioři; Male; algoritmy; Female